Chelerythrine induces apoptosis and ferroptosis through Nrf2 in ovarian cancer cells: Chelerythrine triggers cell death via Nrf2 in ovarian cancer - Zhou, Jia; Wang, Yuchen; Fu, Yangxin; Lin, Zhe; Lin, He; Lv, Guangfu; Kong, Ning; Xin, Guo; Zhou, Fang; Qiu, Zhidong; Huang, Xiaowei (Cellular and Molecular Biology, 2024)
Ovarian cancer is a prevalent malignancy in the female reproductive system, representing a significantly fatal and incurable tumor. Chelerythrine (CHE), a natural benzopyridine alkaloid, has demonstrated a broad spectrum of anticancer activities. Nevertheless, the ovarian cancer inhibitory impact of CHE remains unclear. In this study, we investigated the cytotoxic mechanism and potential targets of CHE on in vitro cultures of A2780 and SKOV3 cells derived from ovarian cancer. Additionally, in vivo experiments were conducted to confirm the suppressive impact of CHE on tumor growth in nude mice. The findings revealed that CHE impeded the growth of A2780 and SKOV3 cells in a concentration-time-dependent manner and significantly suppressed the development of tumors in nude mice. CHE elevated the level of oxidative stress in tumor cells, prompted cell cycle halt in the S phase, and increased their mitochondrial membrane potential. Western blotting results demonstrated that CHE could modulate the expression of proteins associated with apoptotic and ferroptosis processes in A2780 and SKOV3 cells. Nrf2 was verified to be an upstream key target mediating the inhibitory impact of CHE on ovarian cancer cells. In summary, CHE exerts its anti-cancer effects on ovarian cancer by modulating Nrf2, inhibiting cellular proliferation, and promoting apoptosis and ferroptosis.